1. INSOMNIA AND MENTAL HEALTH STATUS AMONG STAFF AND LECTURERS AT PHENIKAA UNIVERSITY (Vietnam Journal of Community Medicine, 2025)
Objectives: To investigate the insomnia and mental health status among staff and lecturers who currently work at Phenikaa University.Methods: A cross-sectional study among 111 staff and lecturers at Phenikaa University using Insomnia Severity Index (ISI) and DASS-21 to collect data from 12/2024 to 03/2025Results: The proportion of insomnia among participants was high (42.3%). Among insomnia participants, nearly 75% were moderate. The proportions of anxiety, depression, and stress were 46,8%; 21,6%; and 26,6% respectively.Conclusion: The prevalence of insomnia and anxiety was high among staff and lecturers; the proportion of stress and depression was also notable. Those results indicate the need for intervention to address sleep and mental health problems in this population.
Keywords: insomnia; depression; anxiety; stress; lecturers; ISI; DASS-21